Research on Dynamic Test of Hyper-Velocity Impact Penetration Acceleration Signal - Debiao Zhang; Jie Li; Xiaokai Wei; Kaiqiang Feng; Yu Wang; Jihe Zhao; Dong Xue (IEEE Access, 2020)
In recent years, with the development of hyper-velocity weapon, the research focus of penetration effect has switched gradually from high-velocity to hyper-velocity, with insufficient studies on penetration effect and its internal mechanism. Besides, the study on penetration effect of hyper-velocity weapon depends on the measurement of mechanical signal during penetration of projectile. In this paper, dynamic test of hyper-velocity impact penetration acceleration signal is studied in depth. Firstly, the penetration velocity and acceleration of projectile under the impact load are analyzed, the influence of the movement of the testing unit on the measured acceleration signal is studied, and the factors to be considered when measuring the hyper-velocity impact load are given. Further, this paper designs a measurement circuit and dynamic models of each measurement module, details the influence of dynamic characteristics of power delivery network on test accuracy, and provides a method to obtain dynamic characteristics of power delivery network by virtue of S parameter. Finally, to extract the real penetration overload signal, a superior noise reduction algorithm adopting Modified Ensemble Empirical Mode Decomposition (MEEMD) is proposed, taking dynamic uncertainty and degree of approximation as evaluation indicators, and the measured sensor data is analyzed and processed with the proposed superior noise reduction algorithm. The experiment results show that, this method has a better noise reduction effect, and can be adopted to effectively extract real penetration overload signal. The results have theoretical research and application value to evaluate the reasonableness and effectiveness of measurement method of hyper-velocity penetration overload signal, and seek for a superior processing method for the noisy penetration overload signal.